Strand properties of Leucaena leucocephala (Lam.) de wit wood - Wan Abdul Rahman, Wan Mohd Nazri; Kasim, Jamaludin; Sudin, Rahim; Mohd Yunus, Nor Yuziah; Abdul Hamid, Hazandy (Academic Journals, 2011)
Leucaena leucocephala (Lam.) de Wit, locally known as “petai belalang”, is widely used in Malaysia as livestock forage, reforestation material, as well as furniture and construction timber. This study investigated the properties of strand from L. leucocephala wood. Beside no study has been carried out on the strand properties of this species to date. Strand properties help to support the suitability and effective use of raw materials in wood composite. The main objective was to determine the strand properties of L. leucocephala as a raw material in the manufacturing of oriented strand board (OSB) under laboratory conditions. The study also aimed to determine the recovery and effect of age and strand size on bulk density, and to evaluate the effects of age and tree portion on strand properties of L. leucocephala from eight and sixteen-year-old trees. A total of 28 trees used in this study were randomly selected. Stranding process separated the fines and sorted the strands into 4 sizes; S0 (25 to 3.2 mm), S1 (19 to 12.7 mm), S2 (12.7 to 6.3 mm) and S3 (6.3 to 3.2 mm). Strand sizes of more than 25 mm and below 3.2 mm were rejected. Results showed that the recovery of strands from eight and sixteen-year-old wood was approximately 75.01 and 70.15%, respectively. Age and strand size were found to affect bulk density significantly. Strand size of S3 from sixteen-year-old gave the highest bulk density (436 g/L) while the lowest bulk density (321 g/L) was shown by strand size of S1 from eight-year-old. The correlation analysis revealed that bulk density showed a positive correlation with increase in age (r = 0.69*). Bulk density also showed a positive correlation with decrease in strand size from S0 to S3 (r = 0.43*). On average, strands from eight-year-old wood (65.90 mm) are longer than that of sixteen-year-old wood (57.64 mm). The average strand thickness from eight and sixteen-year-old wood was 0.90 and 1.00 mm, respectively. The interaction effects of age and strand size also showed significant interaction in area, rectangularity, slenderness ratio and aspect ratio.